Pengembangan Booklet Budidaya Jamur Edible Sebagai Bahan Ajar Mikologi: (Development of Edible Mushroom Cultivation Booklet as Mycology Teaching Materials) - Harlis Harlis; Retni S. Budiarti; Desfaur Natalia (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
This study aims to develop an edible mushroom cultivation booklet in the mycology course. The method used in this research is research and development using the ADDIE model. This research was conducted with the stages of analysis, design, development, implementation, and evaluation. Based on the results of the study, it shows that the feasibility of the booklet used is declared feasible according to the results of media validation and material validation by the validator team. On the results of the first media validation with a score of 75%